2005
DOI: 10.1128/jb.187.9.3214-3226.2005
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharide Sugars Contribute to Biofilm Formation bySalmonella entericaSerovar Typhimurium on HEp-2 Cells and Chicken Intestinal Epithelium

Abstract: Recently, we demonstrated that Salmonella enterica serovar Typhimurium can form biofilm on HEp-2 cells in a type 1 fimbria-dependent manner. Previous work on Salmonella exopolysaccharide (EPS) in biofilm indicated that the EPS composition can vary based upon the substratum on which the bacterial biofilm forms. We have investigated the role of genes important in the production of colanic acid and cellulose, common components of EPS. A mutation in the colanic acid biosynthetic gene, wcaM, was introduced into S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
113
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(121 citation statements)
references
References 41 publications
4
113
0
4
Order By: Relevance
“…Kim & Wei (2009) noticed that flagellar assemply was important during biofilm formation on PVC in different (meat, poultry and produce) broths and on stainless steel and glass in LB broth. Colanic acid, a capsular extracellular polysaccharide, essential for S. Typhimurium biofilm development on epithelial cells was found not to be required for Salmonella biofilm formation on abiotic surfaces (Ledeboer & Jones, 2005;Prouty & Gunn, 2003). Solano et al (2002) showed that colonic acid was important to form a tight pellicle under LB conditions, while it was dispensable under ATM conditions.…”
Section: Molecular Components Of Salmonella Biofilms Formed On Abiotimentioning
confidence: 99%
“…Kim & Wei (2009) noticed that flagellar assemply was important during biofilm formation on PVC in different (meat, poultry and produce) broths and on stainless steel and glass in LB broth. Colanic acid, a capsular extracellular polysaccharide, essential for S. Typhimurium biofilm development on epithelial cells was found not to be required for Salmonella biofilm formation on abiotic surfaces (Ledeboer & Jones, 2005;Prouty & Gunn, 2003). Solano et al (2002) showed that colonic acid was important to form a tight pellicle under LB conditions, while it was dispensable under ATM conditions.…”
Section: Molecular Components Of Salmonella Biofilms Formed On Abiotimentioning
confidence: 99%
“…S. Typhi is known to form biofilms in abiotic and biotic surfaces and it is therefore not surprising that S. Typhi forms biofilms in the gall bladder (Ledeboer & Jones, 2005). Interestingly, however, formation of Salmonella biofilms on gallstones is dependent on the presence of bile (Prouty et al, 2002).…”
Section: Persistencementioning
confidence: 99%
“…During these two latter stages, extracellular polymeric substances (EPS) help biofilm structural development and cell-cell interaction (Costerton et al, 1999). In S. Typhi infected gallbladders, EPS is primarily composed of cellulose, colanic acid, Vi capsular antigen, curli fimbriae, O antigen capsule and biofilm associated proteins (Gibson et al, 2006;GonzalezEscobedo et al, 2011;Jonas et al, 2007;Ledeboer & Jones, 2005). Although the role of some elements in the EPS remain minor, other elements such as cellulose, colonic acid and O antigen capsule are crucial for S. Typhi persistence and biofilm development (Crawford et al, 2008;Prouty & Gunn, 2003;Prouty et al, 2002).…”
Section: Persistencementioning
confidence: 99%
“…These fimbriae are expressed in vitro after static growth for 48 h at 37°C. Our research group has recently demonstrated that these fimbriae are involved in biofilm formation on HEp-2 tissue culture cells, murine intestinal epithelium, and chicken intestinal epithelium (7,37).…”
mentioning
confidence: 99%
“…Environmental signals regulating Tafi biosynthesis proceed through the csgD gene product that directly regulates expression of the major subunit CsgA (8,25,26,57). In addition to regulating expression of Tafi, CsgD also regulates cellulose biosynthesis (8,(24)(25)(26), a component of exopolysaccharides in Salmonella biofilms formed on some surfaces (24,37,53,54,60).…”
mentioning
confidence: 99%